Kalimat Imperatif dalam Film Imperfect: Karier, Cinta dan Timbangan - Muhamad Amang; Irwan Siagian (Journal on Education, 2023)
This study aims to identify, classify imperative forms and analyze imperative sentence functions. This research is a qualitative research. This study uses instruments in the form of human instruments, researchers with all their knowledge regarding the use of Indonesian orally which includes pragmatics in the form of speech. The data source for this research is a film called Imperfect. The results of the study show that: (1.) the imperfect film uses six kinds of imperative sentences. Imperative imperative sentences are the most used in imperfect films, which consist of 21 imperative sentences, 24 imperative sentences of request, 20 imperative sentences of invitation, 3 imperative sentences of hope or request, 8 imperative sentences of prohibition, and 2 imperative sentences of omission.